"Where Is Everybody?" Fermi's Paradox, Evolution, and Sin. Issue 3 (3rd July 2019) - Herzfeld, Noreen
ABSTRACT: The Search for Extraterrestrial Intelligence (SETI) project has been scanning the heavens for signs of intelligent life for almost half a century. So far, nothing. This raises the question physicist Enrico Fermi asked, "Where is everybody?" The probability of intelligent life on another planet is high so why the silence? Technological civilizations may be short-lived. The mechanisms of evolution that lead to intelligent life and technological development also lead to propensities traditionally labeled as sin. These propensities make it difficult for technological civilizations to survive long enough to escape their home planet.